Is breast surgery necessary for breast carcinoma in complete remission following neoadjuvant chemotherapy? - Richter, Hannah; Hennigs, André; Schäfgen, Benedikt; Sohn, Christof; Golatta, Michael; Heil, Jörg (Geburtshilfe und Frauenheilkunde, 2018)
The likelihood of pathological complete remission (pCR) of breast cancer following neoadjuvant chemotherapy (NACT) is increasing; most of all in the triple negative and HER2 positive tumour subgroups. The question thus arises whether or not breast surgery is necessary when there is complete remission after NACT, and whether it provides any improvement of the oncological treatment result when tumour is no longer detectable. Avoiding surgery and possibly even radiotherapy would only be conceivable on the basis of a reliable diagnosis of pCR without operating. Current imaging does not achieve the necessary sensitivity and specificity to assure the diagnosis of pathological complete remission. Further studies are therefore required to determine which methods are best able to evaluate tumour response to NACT. Studies on image-guided, minimally invasive biopsies after NACT have delivered first promising results towards diagnosing pCR before surgery and could provide the basis for further studies on the possibility of avoiding surgery in this specific patient collective.
Gesehen am 04.02.2020